THERMAL INVESTIGATION AT WONOSOBO MARKET, INDONESIA - Hermawan Hermawan (Universitas Pendidikan Indonesia, 2022)
Thermal comfort is one of the factors influencing the success of the building as a place of human activity. Market building in Indonesia plays an essential role in trading activity. The thermal conditions of the Wonosobo market have problems in realizing the thermal comfort of building users. This research aims to investigate the thermal situation of Wonosobo Market, Indonesia. The research method uses quantitative and qualitative methods. Measurements were made using an infrared thermometer. Subjective measures were carried out on 100 respondents. The results show that the Wonosobo Market building has not been able to meet the expectations of building users. The thermal performance of the Wonosobo Market needs to be improved to comfortably accommodate the activities of building users.